Metal tools of the Petrovka Culture of the Southern Trans-Urals and Middle Tobol: chemical and metallurgical characteristics - Degtyareva A.D.; Kuzminykh S.V. (Вестник археологии, антропологии и этнографии, 2022)
In this paper, the chemical composition of tools and ingots of the Petrovka Culture of the Southern Trans-Urals and Middle Tobol region is characterized with identification of main recipes of the alloys using several analytical methods (spectral, X-ray fluorescence, and atomic emission spectrometry analyses carried out in the laboratories of the Institute of Archaeology of the Russian Academy of Sciences and the Institute of Inorganic Chemistry of the Siberian Branch of the Russian Academy of Sciences). The complexes of the Petrovka Culture of the Sou-thern Trans-Urals have been dated by a set of AMS 14C dates to 19th–18th centuries BCE. Recently introduced in the scientific discourse 27 AMS 14C dates (settlement of Stepnoe and burial grounds of Stepnoe 1, 7 and 25) established an earlier interval of the Petrovka series — 2133–1631 BCE and point to the synchroneity of the cultures at the northern periphery of the Sintashta area in the local micro-region of the Southern Trans-Urals. The results of the analytical study of 106 metal tools and 70 ingots of the Petrovka Culture of the Southern Trans-Urals and south of Western Siberia are reported. The statistical processing of the analytical results with plotting correlation diagrams of Sn–As, Sn–Pb, As–Ag, As–Sb, and a frequency distribution histogram for the proportions of Sn allowed casting the metal into 4 metallurgical groups — pure copper and tin, arsenic-tin and arsenic bronzes. The first group subdivided into oxide and sulfidic samples. According to the geochemical peculiarity of the metal from the metal industry centers of Ustie 1, Kulevchi 3 and Shibaevo 1, several sources of oxide-carbonated ores were utilized for copper smelting — malachite and azurite-malachite deposits, while sulfidic chalcocite-covelline ores, and sometimes chalcopyrite-pyrite depositions, were added to the melt as a flux agent. The admixture of sulfides was carried out as an experiment and was not purposeful. Petrovka metallurgists supplied copper to the workshops of the Middle Tobol region — the sites of Ubagan 1, 2, 3 and Kamyshnoe 1, 2. The centers of the Petrovka Culture of the Southern Trans-Urals were dominated by the production of pure copper implements, including the metal smelted from the oxidized ore. To a lesser extent, low-alloyed bronze was used — Cu+Sn, Cu+Sn+As and Cu+As, whose feedstock was supplied by the kindred tribes of Central and Eastern Kazakhstan in the form of ingots and finished products along the eastern part of the Trans-Eurasian transport corridor of metal trade — over the Turgay trough and further along the extensive river system of the Tobol River and its tributaries. The highest concentration of tools of alloyed bronzes was recorded in the burial grounds of the Middle Tobol, which can be explained from the point of view of the prestige value of such goods and observance of special ceremonial practices.